Using a natural experiment to measure the impact of swifter punishment on criminal recidivism - Andersen, Lars Højsgaard (Journal of experimental criminology, 2020)
Measure the impact of swifter punishment on the timing of first imprisonment and on criminal recidivism among young violent offenders.